Parametric study on dual-fuel ignition characteristics under marine engine-relevant conditions. (1st March 2022) - Zhu, Jizhen; Liang, Yueying; Wang, Sixu; Yu, Liang; Zhou, Dezhi; Qian, Yong; Lu, Xingcai
Highlights: Develop a novel parameter-sensitivity method to quantify IDT-dependence. The addition of methanol has a larger impact on DF autoignition than methane. Ambient-charge reactivity is significant to optimize the DF-engine performance. Mixing degree and mixing-time are critical to control the ignition process. High-T IDT-reduction of Methanol-addition due to CH3 OH + HO2 <=> CH2 OH + H2 O2 . Abstract: Dual-fuel (DF) combustion strategies with low-carbon fuels are attractive for the shipping industry because of their better economy and lesser emissions. However, DF ignition process is highly complex and difficult to control due to its strong sensitivities to mixture-states. As such, a comprehensive numerical study was conducted to investigate the influence of thermodynamic states, ambient-fuel reactivity and micro-mixing process on the autoignition characteristics of DF mixtures (methane/ n -heptane and methanol/ n -heptane) under marine engine-relevant conditions. A novel parameter-sensitivity evaluation method by log–log definition was firstly proposed to quantify the ignition-delay-time (IDT) dependence on thermodynamic trajectory and charge reactivity, based on a newly detailed kinetic model (NUIGMech1.1). It was found that the methanol-addition has a larger impact on IDTs than methane, and also exhibits ignition-promoting behaviors at high temperatures. Besides, the IDT displays a higher sensitivity to temperature under methanol/air atmosphere but a higher sensitivity to pressure under methane/air atmosphere, suggesting that methane/diesel DF engines are prone to occur cycle-to-cycle variations under diesel pilot-ignition (DPI) mode while methanol/diesel DF engines exist the larger cycle variations under reactivity-controlled compression-ignition (RCCI) mode. There are small IDT-changes for methane/ n -heptane mixtures with varying ϕCH4 while large variations for methanol/ n -heptane as varying ϕCH3OH . Moreover, methanol shows the more significant chemical-effect on ignition. The mixture fraction of methanol-based blends with the shortest IDT, defined as the most-reactive mixture fraction ( Z MR ), is larger than that of methane at a given temperature. This demonstrates that the mixing degree (the high-reactivity fuel to low-reactivity fuel ratio) plays an important role in controlling the ignition. The mixing-time is also critical for ignition behavior of fuels, and autoignition of methanol/ n -heptane blends exhibits higher sensitivity to mixing rates than methane/ n -heptane. Therefore, adjusting injection parameters could tailor mixing-trajectories to offset changes in fuel autoignition chemistry. Additional reaction sensitivity analyses demonstrate that the OH radicals play a key role in the whole system reactivity at low temperatures, while HO2 becomes more important at intermediate-temperatures and CH3 OH + OH <=> CH2 OH + H2 O displays the highest ignition-inhibition. Significantly, CH3 OH + HO2 <=> CH2 OH + H2 O2 shows a high promoting effect on IDTs at high temperatures, resulting in the IDT-reduction.